Religious Coping and Family Quality of Life Among Parents of Children With Intellectual Disabilities: Testing the Mediating Role of Mindfulness. - Hu, Xiaozhong; Cheng, Sanyin; Li, Xuxu (Journal for the Scientific Study of Religion (John Wiley & Sons, Inc.), 2025)
This study focused on the relationships among religious coping, mindfulness, and family quality of life among parents of children with intellectual disabilities in mainland China. Questionnaires on religious coping, mindfulness, and family quality of life were administered to parents of 189 children with intellectual disabilities. The results showed that religious coping directly and indirectly predicted family quality of life, mediated by mindfulness. The contribution, limitations, and influence of this study are discussed.